Analisis Faktor Indeks Harga Konsumen (IHK) Menurut Kelompok Pengeluaran yang Mempengaruhi Laju Inflasi Provinsi Lampung Tahun 2020 - Ayu Aprianti; Tiara Shofi Edriani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
The Consumer Price Index (CPI) is used as the basis for calculating regional inflation rates. The balance of the CPI variable by Expenditure Group (CPI-EG) needs to be considered so that it does not have a major impact on the inflation rate. The purpose of this study is to determine the CPI-EG variable that affects the inflation rate in Lampung Province using the factor analysis method through the extraction technique of Principal Component Analysis. Factor analysis aims to reduce the CPI-EG variable into a factor with a smaller number. Based on the result of factor analysis there are 3 CPI-EG variables that were reduced because they did not meet the feasibility test and 8 CPI-EG variables that could be analyzed further. These variables form 1 factor which is named the Community Supporting Needs Factor. These factors can explain 79,304% of the total variance. Of the 8 CPI-EG variables, the Health Variable is the most dominant effect on the inflation rate in Lampung Province with a strong correlation of 0,980. This inflation rate is due to public health needs due to the increase in Covid-19 cases in Lampung Province in 2020.